SLC11A1 promoter gene polymorphisms and fibrosis progression in chronic hepatitis C. Issue 3 (11th February 2004) - Romero-Gómez, M; Montes-Cano, M A; Otero-Fernández, M A; Torres, B; Sánchez-Muñoz, D; Aguilar, F; Barroso, N; Gómez-Izquierdo, L; Castellano-Megias, V M; Núñez-Roldán, A; Aguilar-Reina, J; González-Escribano, M F
Abstract : Background and aims: The solute carrier family 11 member 1 (SLC11A1) gene (formerly Nramp1) encodes for the protein solute carrier family 11, member 1. It affects susceptibility and clinical outcome of autoimmune and infectious diseases. We investigated the possible role of the functional polymorphism located in the promoter region of SLC11A1 and tumour necrosis factor (TNF) genes in the progression of fibrosis in chronic hepatitis C. Methods: A total of 242 Caucasian Spanish patients with biopsy proven chronic hepatitis C and 194 healthy control subjects were genotyped for SLC11A1 and TNF promoter polymorphisms. Results: No significant differences in the distribution of frequencies among patient and control groups were observed. The SCL11A1 homozygous 2/2 genotype was rarely detected among patients showing advanced fibrosis (2/82; 2.4%) but was highly represented in those with mild fibrosis (29/160; 18.1%; odds ratio (OR) 8.85 (95% confidence interval (CI) 1.9–55.2, pc  = 0.002). In patients carrying allele 3 of SLC11A1, the presence of −238 TNF A/G was associated with advanced fibrosis (14/26 (53.8%) v 68/216 (31.4%); OR 2.53 (95% CI 1.03–6.23); p = 0.02). Conclusions: SLC11A1 gene promoter polymorphism could influence fibrosis progression in chronic hepatitis C in that the homozygous genotype 2/2 exerts a protective effect against cirrhosis development. Also, the combination of TNF −238 A/G and the presence of allele 3 is conducive to progression to pre-cirrhotic or cirrhotic stages of the disease.